Towards A Halal Certification Module And Training Programme Development For The Pharmaceutical Industry - N.A. Khairun Nain; A.H. Nazefah; C.I. Che Ilina; M.R. Mohd Dzulkhairi; Z. Noor Fadzilah; Z. Norlelawati; A.A. Asral Wirda; A.M. Normaliza; M. Ahmad Wifaq; A.A. Siti Hanizah; A.K. Imtinan; M.S. Norhaizam; et al. (IDOSI Publications, 2024)
Non-Indexed Publication